Reconfiguring Sufi Ethics in Economic Life: Discursive Tradition and Moral Rationality in Contemporary Indonesian Tarekat - Kurniawan, Ade Fakih; Saraswati, Henny; Soi, Andi Bahri; Megandani, Adi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2026)
The relationship between Sufi ethics and economic rationality has long been framed as structurally incompatible, with classical concepts such as zuhd, faqr, ṣabr, and tawakkul interpreted as theological warrants for withdrawal from commercial life. Reinforced by Weber’s thesis on the absence of inner-worldly asceticism in Islam, this assumption has produced a persistent tendency to treat Sufism as economically passive. This article challenges that position by examining how these concepts are actively reconfigured within the economic practices of contemporary tarekat communities in Indonesia. Drawing on ethnographic fieldwork combining participant observation, in-depth interviews, and classical textual analysis in the Tarekat Qādiriyyah wa Naqshbandiyyah (TQN) in Banten and the Tarekat Khalwatiyyah in South Sulawesi, this study finds that zuhd, faqr, ṣabr, and tawakkul are continuously reinterpreted to authorize disciplined, morally grounded economic engagement. To explain this transformation, the article deploys Talal Asad’s concept of discursive tradition alongside an integrated model of ideational and structural relations. The findings demonstrate that Sufi traditions articulate a distinct ethical rationality that motivates productive and ethically bounded economic conduct, constituting an empirical challenge to Weber’s Protestant-centric framework.